Percutaneous Ablation of Adrenal Tumors - Venkatesan, Aradhana M. (2010)
Adrenal tumors comprise a broad spectrum of benign and malignant neoplasms, and include functional adrenal adenomas, pheochromocytomas, primary adrenocortical carcinoma and adrenal metastases. Percutaneous ablative approaches that have been described and used in the treatment of adrenal tumors include percutaneous radiofrequency ablation (RFA), cryoablation, microwave ablation and chemical ablation. Local tumor ablation in the adrenal gland presents unique challenges, secondary to the adrenal gland’s unique anatomic and physiologic features. The results of clinical series employing percutaneous ablative techniques in the treatment of adrenal tumors are reviewed in this article. Clinical and technical considerations unique to ablation in the adrenal gland are presented, including approaches commonly used in our practices, and risks and potential complications are discussed.